2010
DOI: 10.1002/poc.1786
|View full text |Cite
|
Sign up to set email alerts
|

Interaction studies of cysteine with Li+, Na+, K+, Be2+, Mg2+, and Ca2+metal cation complexes

Abstract: The coordination geometries, electronic features, metal ion affinities, entropies, and the energetics of Li+, Na+, K+, Be2+, Mg2+, and Ca2+ metal cations with different possible conformations of cysteine complexes were studied. The complexes were optimized using density functional theory (B3LYP) and second order Moller–Plesset Perturbation (MP2) theory methods using 6‐311 + +G** basis set. The interactions of the metal cations at different nucleophilic sites of cysteine conformations were considered after a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…54,55 At that, a metal ion can coordinate both a special functional group of SM and a few groups together. 56 Therefore, the silver mercaptide aggregates that belong to complexes containing also metal ions interact with water molecules other than those that are in the unbound state, since functional groups coordinated by metal ions do not form hydrogen bonds with water. [57][58][59] We can conclude that the addition of salt leads to the coordination of some functional groups by metal ions on the surface of SM supramonomers.…”
Section: Model Of Gelation In Cssmentioning
confidence: 99%
“…54,55 At that, a metal ion can coordinate both a special functional group of SM and a few groups together. 56 Therefore, the silver mercaptide aggregates that belong to complexes containing also metal ions interact with water molecules other than those that are in the unbound state, since functional groups coordinated by metal ions do not form hydrogen bonds with water. [57][58][59] We can conclude that the addition of salt leads to the coordination of some functional groups by metal ions on the surface of SM supramonomers.…”
Section: Model Of Gelation In Cssmentioning
confidence: 99%
“…Authors used electrospray ionization (ESI) coupled to MS to characterize the resulting complexes and confirmed the high affinity of cobalt(II) towards the sulfur atom. Energetic studies involving interactions of cysteine with alkali metal cations, Be 2+ , Ca 2+ and Mg 2+ , have also been published . Concerning the interactions between organotins and cysteine, various studies using potentiometry and Mössbauer spectroscopic methods have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Energetic studies involving interactions of cysteine with alkali metal cations, Be 2+ , Ca 2+ and Mg 2+ , have also been published. [28][29][30][31][32][33] Concerning the interactions between organotins and cysteine, various studies using potentiometry [13,14] and Mössbauer spectroscopic methods have been reported. [15][16][17] To the best of our knowledge, the interactions taking place between OTCs and cysteine have not been explored so far by MS, and this is the purpose of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…It must involve a different path. It is well known that L-cysteine has antioxidant ability (31) and coordination ability with metallic ion (32), and thus hindering dexoy-hemoglobin or/and oxy-hemoglobin from oxidation. As for α-lactose, it might be related to its reducing property or its water retention ability during dehydration (23), thereby limiting oxygen accessibility to heme iron (33).…”
Section: Resultsmentioning
confidence: 99%